Rancang bangun kendali beban listrik berbasis Internet of Things (IoT) - Nur Khafidhoh; Nur Holis (JOURNAL SAINS STUDENT RESEARCH, 2026)
Electrical overload in small-scale power installations may cause equipment damage and increase fire risk. This study aims to design and implement an Internet of Things (IoT)-based electrical load control system by applying a priority logic mechanism. The research method used is a descriptive qualitative approach with a prototyping development model. The system is developed using an ESP32 microcontroller as the main controller, a PZEM-004T current sensor for current measurement, and relay modules for load disconnection. The Blynk application is utilized for real-time monitoring and remote load management. The results show that the system is capable of monitoring electrical current in real time and performing gradual load shedding based on predefined priority levels during overload conditions. This system provides an effective solution to improve electrical safety and efficiency in load management